2022
DOI: 10.3389/fbioe.2022.978554
|View full text |Cite
|
Sign up to set email alerts
|

The application of finite element analysis to determine the optimal UIV of growing-rod treatment in early-onset scoliosis

Abstract: Objectives: To analyze the stress distribution in the proximal vertebral body and soft tissue of dual growing-rod (GR) with different upper instrumented vertebra (UIV) to determine the optimal UIV.Methods: A ten-year-old male EOS case treated with GR was selected. Based on spiral computed tomography (CT) scanning performed in 0.6 mm thick slices, a finite element model (FEM) of the preoperative state (M0, the original spine state) of the patient was created. Subsequently, four models with different UIV fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…By simulating postoperative loading conditions under physiological conditions during walking, cyclic loading can be used to create a similar model for studying screw pullout in patients with osteoporosis. Pan and Buell et al [22,23] constructed a finite element model of spinal deformity internal In this study, 3 finite element models of osteoporotic kyphosis with neurological dysfunction were successfully created, and their validity was confirmed by comparing the range of motion of normal segments with that of normal models. The results showed that the internal fixation stress and internal displacement in the BDBO group were significantly higher than those in the other 2 groups, and the stress on the titanium mesh reached 1328 MPa under left flexion conditions.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…By simulating postoperative loading conditions under physiological conditions during walking, cyclic loading can be used to create a similar model for studying screw pullout in patients with osteoporosis. Pan and Buell et al [22,23] constructed a finite element model of spinal deformity internal In this study, 3 finite element models of osteoporotic kyphosis with neurological dysfunction were successfully created, and their validity was confirmed by comparing the range of motion of normal segments with that of normal models. The results showed that the internal fixation stress and internal displacement in the BDBO group were significantly higher than those in the other 2 groups, and the stress on the titanium mesh reached 1328 MPa under left flexion conditions.…”
Section: Discussionmentioning
confidence: 80%
“…By simulating postoperative loading conditions under physiological conditions during walking, cyclic loading can be used to create a similar model for studying screw pullout in patients with osteoporosis. Pan and Buell et al [ 22 , 23 ] constructed a finite element model of spinal deformity internal fixation to simulate vertebral load. Through local mechanical distribution, local displacement, and other conditions of fixed segments, they analyzed the occurrence of Proximal Junctional Kyphosis (PJK) after spinal deformity correction surgery from a mechanical perspective, and obtained reliable data.…”
Section: Discussionmentioning
confidence: 99%